What's Another Day? The Effects of Wait Time for Substance Abuse Treatment on Health-Care Utilization, Employment and Crime - Jenny Williams; Anne Line Bretteville-Jensen (Institute of Labor Economics (IZA), 2022)
This research provides the first evidence on the impacts of waiting times for treatment for a substance use disorder (SUD). Using rich linked administrative information from Norway, we study the impact of waiting time on health-care utilization, employment and crime for patients who enter outpatient treatment for cannabis use disorder. Confounding due to unobserved severity of illness is addressed using an instrumental variables strategy that exploits plausibly exogenous variation in congestion in Norway's health-care system. We find that waiting to access treatment increases the use of health-care services at both the extensive and intensive margins, measured by the duration of a treatment episode and the number of consultations within a treatment episode, respectively. Waiting time also has spill-over effects, reducing employment after entering treatment and increasing crime both before and after treatment begins. Together, these findings suggest that waiting times to access treatment for a SUD imposes significant costs on patients, health-care systems, and on society more broadly.
Keywords: I12; J22; K42; 330; waiting times; cannabis; substance use treatment; employment; crime